SITUATED REFLECTIONS ON INTERNATIONAL LABOUR LAW, CAPABILITIES, AND DECENT WORK: THE CASE OF CENTRE MARAÎCHER EUGÈNE GUINOIS - Blackett, Adelle (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2007)
This article engages the contemporary transformation of international labour normativity by refocusing debates between civil/political rights and economic/social rights on a contextualized discussion on social inequalities. It traces the persistent labour market inequality experienced by one historically marginalized group, the black community in Canada, though the lens of a particularly problematic recent human rights decision. It first contends that efforts to reconceptualize labour law as fundamentally procedural in nature run the risk of undermining attempts to protect the economic and social rights of those most in need of labour law. It adds that neither are economic and social rights a panacea. Instead it suggests that notions of equality and decent work must play a guiding role in rethinking the indivisibility of rights, to ensure that labour law (national and transnational) fulfil both its protection and worker empowerment mandates.